Peran Mediasi Motivasi Kerja dalam Hubungan Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kinerja Pegawai pada Sektor Publik - Nelly Miranda; Lukman Ibrahim; Kurnia Asni (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2026)
This study investigates the effects of leadership style and the work environment on employee performance, with work motivation serving as a mediating variable, at the Aceh Department of Manpower and Population Mobility. Using an explanatory quantitative research design, data were collected from 155 employees selected from a population of 252 through proportionate stratified random sampling based on the Slovin formula. A structured questionnaire employing a five-point Likert scale was used for data collection, and the proposed model was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that leadership style and the work environment do not have significant direct effects on employee performance. However, both variables exert positive and significant effects on work motivation. In turn, work motivation has a strong and significant positive effect on employee performance. Furthermore, mediation analysis confirms that work motivation fully mediates the relationships between leadership style and employee performance as well as between the work environment and employee performance. These results indicate that employee performance in public sector organizations is driven primarily by employees' intrinsic motivation rather than by organizational factors alone. Consequently, initiatives aimed at improving employee performance should prioritize strategies that strengthen work motivation while simultaneously fostering supportive leadership practices and a conducive work environment. This study extends the organizational behavior literature by demonstrating the critical mediating role of work motivation in explaining employee performance within the public sector. The findings also provide practical insights for public human resource managers in designing policies and managerial interventions that enhance employee motivation and ultimately improve organizational performance.